Superior Personality and Sustainability of Wisdom UMPSA aims 6 commitments, 20 initiatives - Nor Salwana, Mohammad Idris (UMPSA, 2024)
GAMBANG, 16 February 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has the capacity in terms of resources, talent and expertise to enable the university to realise its vision and mission.